Multifaceted regulation of T cells by CD44 - Bas J.G. Baaten; Cheng-Rui Li; Linda M. Bradley (Communicative & Integrative Biology, 2010)
CD44 is a widely-expressed adhesion receptor that is associated with diverse biological processes involving migrating cells, including inflammation, angiogenesis, bone metabolism, and wound healing. In the immune system, CD44 is upregulated after activation of naive T lymphocytes during their responses against invading microbes. Once an infection is cleared, elevated levels of CD44 remain on the surface of memory T cells that mediate protection against re-infection. While this has led to the use of highly sustained CD44 expression on T cells as an indicator of a previous immune response, the relevance to T-cell responses or homeostasis has been largely unexplored. Our recent studies demonstrate that CD44 selectively regulates the survival of the Th1 subset of CD4 T cells, but not other T-cell subpopulations. These findings, together with studies of CD44 in other cell types, suggest that differences in the engagement of signaling mechanisms are likely to underlie differential regulation of T-cell responses and underscore the importance of this adhesion receptor to immune cell regulation and protection against viruses and intracellular bacteria.